Identification of the initiation site of poliovirus polyprotein synthesis. - Dorner, A J (1982)
The complete nucleotide sequence of poliovirus RNA has a long open reading frame capable of encoding the precursor polyprotein NCVP00. The first AUG codon in this reading frame is located 743 nucleotides from the 5' end of the RNA and is preceded by eight AUG codons in all three reading frames. Because all proteins that map at the amino terminus of the polyprotein (P1-1a, VP0, and VP4) are blocked at their amino termini and previous studies of ribosome binding have been inconclusive, direct identification of the initiation site of protein synthesis was difficult. We separated and identified all of the tryptic peptides of capsid protein VP4 and correlated these peptides with the amino acid sequence predicted to follow the AUG codon at nucleotide 743. Our data indicate that VP4 begins with a blocked glycine that is encoded immediately after the AUG codon at nucleotide 743. An S1 nuclease analysis of poliovirus mRNA failed to reveal a splice in the 5' region. We concluded that synthesis of the poliovirus polyprotein is initiated at nucleotide 743, the first AUG codon in the long open reading frame.